Depression, Anxiety, and Cigarette Smoking Among Patients with Tuberculosis. (January 2023) - Jones-Patten, Alexandria; Wang, Qiao; Molebatsi, Keneilwe; Novotny, Thomas E.; Siddiqi, Kamran; Modongo, Chawangwa; Zetola, Nicola M.; Mbongwe, Bontle; Shin, Sanghyuk S.
Smoking adversely affects tuberculosis (TB) outcomes and may be associated with depression and anxiety among people diagnosed with TB in Botswana. We conducted a cross-sectional study among patients newly diagnosed with TB in Gaborone, Botswana, evaluating factors associated with self-reported cigarette smoking. We performed Poisson regression analyses with robust variance to examine whether depressive and anxiety symptoms were associated with smoking. Among 180 participants with TB enrolled from primary health clinics, depressive symptoms were reported in 47 (26.1%) participants and anxiety symptoms were reported in 85 (47.2%) participants. Overall, 45 (25.0%) participants reported current smoking. Depressive symptoms were associated with a higher prevalence of smoking (adjusted prevalence ratio [aPR]: 2.04; 95% confidence interval [CI]: 1.29–3.25) in the adjusted analysis. The association between anxiety symptoms and smoking did not reach statistical significance (aPR: 1.26; 95% CI: 0.77–2.05). Future studies should further investigate these associations when addressing TB care.